The Drosophila TNF receptor Grindelwald couples loss of cell polarity and neoplastic growth. - Andersen, D.S.; Colombani, J.; Palmerini, V.; Chakrabandhu, K.; Boone, E.; Röthlisberger, M.; Toggweiler, J.; Basler, K.; Mapelli, M.; Hueber, A.O.; Léopold, P. (Nature, 2015)
Disruption of epithelial polarity is a key event in the acquisition of neoplastic growth. JNK signalling is known to play an important part in driving the malignant progression of many epithelial tumours, although the link between loss of polarity and JNK signalling remains elusive. In a Drosophila genome-wide genetic screen designed to identify molecules implicated in neoplastic growth, we identified grindelwald (grnd), a gene encoding a transmembrane protein with homology to members of the tumour necrosis factor receptor (TNFR) superfamily. Here we show that Grnd mediates the pro-apoptotic functions of Eiger (Egr), the unique Drosophila TNF, and that overexpression of an active form of Grnd lacking the extracellular domain is sufficient to activate JNK signalling in vivo. Grnd also promotes the invasiveness of Ras(V12)/scrib(-/-) tumours through Egr-dependent Matrix metalloprotease-1 (Mmp1) expression. Grnd localizes to the subapical membrane domain with the cell polarity determinant Crumbs (Crb) and couples Crb-induced loss of polarity with JNK activation and neoplastic growth through physical interaction with Veli (also known as Lin-7). Therefore, Grnd represents the first example of a TNFR that integrates signals from both Egr and apical polarity determinants to induce JNK-dependent cell death or tumour growth.